Mesenteric ischaemia: the endovascular management - Aste S., Hernán (2021)
Mesenteric ischaemia is a condition that may be very severe and potentially lethal particularly in the acute presentation. Early treatment is crucial. We present four consecutive cases managed by our team with thrombosis or dissection or aneurysm of the superior mesenteric artery and the celiac trunk reviewing indications and treatment implemented. Multiple successful endovascular procedures were used in all cases avoiding progression to lethal consequences. None of the patients required an open surgical procedure. Therefore, endovascular procedures are feasible in these patients avoiding intestinal necrosis as well as the need for open surgeries.